Peer-to-Peer-based Web Services for Collaborative Engineering Environments - Schattkowsky, Tim; Loeser, Christoph; Müller, Wolfgang (Proceedings of the International Conference on Networking (ICN 2004), Guadeloupe (France))

Integrated Solar Home System - Krauter, Stefan; Ochs, F. (Renewable Energy)

Considerations for the Calculation of Greenhouse Gas Reduction by Photovoltaic Solar Energy - Krauter, Stefan; Rüther, R. (Renewable Energy Vol. 29, Issue 3 (2004), S. 345–355.)

Development of an integrated solar home system - Krauter, Stefan (Solar Energy Materials & Solar Cells)

Increased electrical yield via water flow over the front of photovoltaic panels - Krauter, Stefan (Solar Energy Materials & Solar Cells)

Remote PV-system monitored via satellite - Krauter, Stefan; Depping, T. (Solar Energy Materials & Solar Cells)

Future Visions - Krauter, Stefan (Words into Action – The International Conference for Renewable Energies – Bonn 2004, Faircount, London (UK), S. 175)

Renewable Energies in Latin America - Krauter, Stefan (Proceedings of the Second World Renewable Energy Forum, Eurosolar, Bonn (Deutschland), 29.–31. Mai 2004)

Enhanced Integrated Solar Home System - Krauter, Stefan (Proceedings of the 19th European Photovoltaic Solar Energy Conference and Exhibition, Paris (Frankreich), 7.–11. Juni 2004, S. 2399–2402)

Photovoltaics in the Context of Carbon Trading - Krauter, Stefan (Proceedings of the 19th European Photovoltaic Solar Energy Conference and Exhibition, Paris (Frankreich), 7.–11. Juni 2004, S. 3523–3526)

Cost Reduction and Increase of Reliability for Remote PV-Systems by Satellite - Krauter, Stefan; Depping, T. (Proceedings of the 19th European Photovoltaic Solar Energy Conference and Exhibition, Paris (Frankreich), 7.–11. Juni 2004, S. 3527–3530)

PV in Combination with Micro Wind Turbines for Rural Household Electrification in the Northeast of Brazil - Krauter, Stefan; Calvacante, F. S. A.; Cunha, M. S.; de Lima, L. C. (Proceedings of the 19th European Photovoltaic Solar Energy Conference and Exhibition, Paris (Frankreich), 7.–11. Juni 2004, S. 3532)

Renewable Energy in Latin America - Krauter, Stefan; Kissel, J. (Renewable Energy World)

Activities concerning the Set-up of an International University for Renewable Energy - Krauter, Stefan (Proceedings of the International Seminar on Hydrogen Technologies, Buenos Aires (Argentina), 7.–9. September 2004)

Security Aspects of Internet Voting - Schryen, Guido (37th Annual Hawaii International Conference on System Sciences)
Voting via the Internet has become a feasible option for political as well as non-political ballots. However, there are many obstacles which have to be overcome, especially legal restrictions have to be transformed into technical and security solutions. The article starts with a brief presentation of advantages and disadvantages of Internet ballots and presents application fields and pilot schemes. Then, technological security aspects are derived due to democratic basic principles. Especially the applied voting procedures are critical in security terms. Hence, the most relevant cryptographic protocols are presented and their drawbacks and shortcomings are identified. However, this article does not propose a new voting protocol. Beyond fixing cryptographic procedures for ballots, more elements are to be specified, e.g. responsibilities and rights of involved authorities or security precautions regarding hardware and software. For this reason, a structural security framework for electronic voting systems is presented which can be used for their composition and analysis.

Internationalisierung mittelständischer Unternehmen: Fünf Thesen zum Auslandsmarkterfolg - Kabst, Rüdiger

International komparatives Personalmanagement: Evidenz, Methodik & Klassiker des "Cranfield Projects on International Human Resource Management" - Kabst, Rüdiger; Brewster, C (Handwörterbuch des Personalwesens)

The Netherlands and Germany: Flexibility or Rigidity - Dietz, B; Hoogendoorn, J; Kabst, Rüdiger; Schmelter, A (Human Resource Management in Europe: Evidence of Convergence?)

Transaktionskostentheorie: Einführung, kritische Diskussion und Ansätze zur Weiterentwicklung - Kabst, Rüdiger (Personaltheorie als Beitrag zur Theorie der Unternehmung)

Theoretical Perspectives for Human Resource Management: The German Discussion - Kabst, Rüdiger; Weber, W (Management Revue: The International Review of Management Studies.)